2018
DOI: 10.21776/ub.jels.2018.008.02.05
|View full text |Cite
|
Sign up to set email alerts
|

Growth Rate and Chemical Composition of Secondary Metabolite Extracellular Polysaccharide (EPS) in Microalga Porphyridium cruentum

Abstract: Porphyridium cruentum microalgae have great potential to be developed as a source of active ingredients in various fields of health. It excretes secondary metabolites in the form of extracellular polysaccharides (EPS), potentially as antibacterial, antihyperglycemic, and immunostimulant components. This study aims to obtain the best culture density of P. cruentum, the active component of P. cruentum (EPS), and the chemical composition of EPS. The P. cruentum was cultivated on 15%, 20% and 25% culture stock, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…In our previous study [15], we reported on P. cruentum growth and extracellular polysaccharides or exopolysaccharides production from this species. Microalgae growth was observed every day for 14 days of culturing, with the provision of 1ml/L of Fe, silicate, and vitamins, and 24-h continuous lighting.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In our previous study [15], we reported on P. cruentum growth and extracellular polysaccharides or exopolysaccharides production from this species. Microalgae growth was observed every day for 14 days of culturing, with the provision of 1ml/L of Fe, silicate, and vitamins, and 24-h continuous lighting.…”
Section: Introductionmentioning
confidence: 94%
“…After 14 days of microalgae culturing, with densities of 15%, 20% and 25%, respectively, we had produced exopolysaccharides of 10,000 mg/L, 12,000 mg/L and 14,000 mg/L, respectively. The Fourier transform infrared spectroscopy (FTIR) test reported in our previous study showed that exopolysaccharides of P. cruentum consist of dominant bonds, namely phenol bonds and polysaccharide bonds [15].…”
Section: Introductionmentioning
confidence: 99%
“…The FTIR test reported in our previous study showed that in EPS there were dominant bonds, namely phenol bonds and polysaccharide bonds [16]. Polysaccharides, one of the ingredients that can be used to produce immunostimulant, are classified into carbohydrates.…”
mentioning
confidence: 99%
“…In our previous study [16], we reported about Porphyridium growth and Extracellular Polysaccharides (EPS) production from this species. Microalgae growth was observed every day for 14 days of culture with the provision of 1ml/L of Fe, silicate, and vitamins and 24-hours continuous lighting.…”
mentioning
confidence: 99%
See 1 more Smart Citation